The Efektivitas Media Ladder Drill Meningkatkan Motivasi Belajar Lari Cepat - Peranita, Nita; Lengkana, Anggi Setia; Supriyadi, Tedi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to determine the effectiveness of ladder drill media in increasing motivation to learn sprinting at the Cinarengta Sumedang State Elementary School. This research uses a quantitative approach with experiments, meaning that a sample is given a treatment. The research design used was One Group Pretest- Posttest Design. The research involved 22 samples, with 13 men and nine women. This research has several stages, the first of which is a pretest; this stage is to see students' motivation before being given treatment using a learning motivation questionnaire, and the second stage is given treatment with ladder drill exercises for 12 meetings. The third stage is the posttest, which looks at the results after being given treatment to see an increase in motivation using a learning motivation questionnaire—a random sampling technique. Based on the results of the Shapiro-Wilk normality test, the overall pretest and posttest data show that the pretest sig value is 0.136 (p<0.05), posttest 0.365 (p<0.05), so it can be concluded that the values ​​are normally distributed. Then, it was tested using a paired sample t-test, and the average increase was -6.5000. The sig-paired t-test value is <0.05, which is 0.000. then there are results. Ngain Score is 0.7, which means 0.7>0.76, which is effective. The Percent Value is 76.4773%, which is >76%, meaning the treatment is effective. With a percentage increase of 33%, these results show that the influence of ladder drill media increases motivation to learn to run fast. In conclusion, there is an increased motivation to learn to run fast with effective results. Keyword: ladder drill, fast running, motivation to learn